BANK SYARIAH INDONESIA SERVICE QUALITY: SOCIAL PERSPECTIVE - Yusuf, Mohammad; Ichsan, Reza Nurul; Rangkuty, Dewi Mahrani (Jurnal Kajian Ekonomi dan Kebijakan Publik (JEpa), 2021)
: Indonesian Sharia Bank is a company engaged in services whose business activities accept money deposits, lend money, and remittance services, but the system of activities is based on Islamic law as stipulated in the Qur‟an and Hadith.  As a service provider, Sharia banking must be able to satisfy customers and provide quality services.   With optimal service quality, it is expected that the party that provides banking services will be able to meet the expectations of its customers, able to win competition that will eventually earn maximum profit. The quality of service is any action or activity that can be offered by a party to another party, which is fundamentally intangible and does not result in any ownership. The result of good quality of service is the result of a comparison between expectations and services in real terms received by consumers.  This study aims to analyze the quality of service and customer satisfaction at Bank Syariah Indonesia by using the Servqual method. This study uses six independent variables namely compliance, assurance, reliability, tangible, emphaty, and responsiveness with one dependent variable that is customer satisfaction.  After conducting a review of libraries and fields and the preparation of hypotheses, the data in this study was collected through the dissemination of questionnaires to 94 customers at the time of conducting transactions at Syaariah Indonesia Banking as a research sample. The sampling technique used is accidental sampling, and the technique used to determine the sample is by using slovin formula.  The data analysis method used is quantitative analysis, namely validity and reliability test, kolmogorov smirnov normality test, paired sample t-test hypothesis test, and gap analysis.  Based on the data analysis, the results showed that the indicators in this study are valid and reliable.